Study on the efficacy of hepatitis B virus vaccination and its influencing factors among children in rural area of Jiangsu province - Zhai, Xiang-jun; Wang, Hua; Zhu, Feng-cai; Yu, Jia-xi; Chen, Yin-zhong; Qiu, Xiang-peng; Gu, Shan-Kun; Liu, She-lan; Qin, Li-ming; Liang, Zheng-lun; Zhuang, Hui (Zhōnghuá liúxíngbìng zázhì, 2007)
To evaluate the efficacy of hepatitis B viruse (HBV) vaccination and its influencing factors among children in rural area of Jiangsu province. Twenty-five hundred and twenty-two children born after 1998 in rural area were selected as the study population using multistage cluster sampling method. HBsAg and anti-HBs were detected by enzyme linked immunoassay (ELISA) and radio-immunoassay (RIA), respectively. Anti-HBs negative children were boosted using different hepatitis B vaccines and the efficacy was compared. Factors causing HBV infection in HBsAg positive children were also investigated. HBsAg positive rates in 1-7 year olds were 0.28%-1.28%, and the anti-HBs positive rates decreased from 76.7% to 45.5%. The HBsAg positive rate in children not timely vaccinated was significantly higher than those with HBV vaccine injection within 24 hours after birth (1.4% vs. 0.5%, P = 0.031). More than 90% of the anti-HBs negative children had protective level of anti-HBs after boosted with HBV vaccine. HBsAg positive r